The Problematics Of The Dipasiala Customary Marriage Tradition: A Case Study And Its Implications - Wijaya, Sandy; Sarkowi, Sarkowi; Tenri, Besse; Zulfahmi, Zulfahmi; Najmii, Muhammad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The Dipasiala tradition is a cultural practice that plays an important role in the Bugis community in Air Solok Batu Village, South Sumatra. However, the application of this custom often leads to divorce when it is done under duress. This study aims to analyse the problems that arise in relation to the Dipasiala custom, as well as to identify the position of the custom from the perspective of urf in the context of Islamic law. The method used is qualitative with in-depth interview techniques and participatory observation, which aims to explore the factors that influence the implementation of the custom, such as changes in social values, tensions between local traditions and Islamic legal principles, and challenges in maintaining cultural heritage in the midst of modernisation. The results of this study show that the theory of ‘urf as a theory in the study of Islamic law sees in terms of its validity that the dipasiala tradition carried out by the Bugis community in Air Solok Village has the potential to fall into the category of ’urf fasid, if the dipasiala tradition is carried out by coercion and the marriage ends in divorce. Then the implications of this research have a significant impact on academics and practitioners of Islamic law in formulating policies that are more sensitive to local cultural values, as well as for the community to maintain the sustainability of this tradition while still considering the principles of justice and harmony with Islamic law. This research also contributes to efforts to maintain the relevance of the Dipasiala tradition in maintaining the cultural identity of the Bugis community in South Sumatra in the era of globalisation.